Unusual inguinal hernia in a middle-aged patient: when the ovary and fallopian tube pass through the inguinal canal. A case report. - Vicente López, Marta; Baeza Carrión, Ana; Velayos García, Paula (Cirugía del Uruguay, 2024)
Inguinal hernia represents the most common pathology of the abdominal wall currently. In the hernia sac, various structures can be found, such as preperitonealphat, smallbowel, colon, oreventhebladder, butthepresenceofthefallopiantubeandovaryisuncommon. Tubo-ovarian content is a frequent finding in pediatric population, while infection is extremely rare in women of reproductive or menopausal age, requiring essential treatment to prevent complications related to fertility and adnexal viability. In order to review the literature described in this regard, given the infrequency of this finding in adult women, we present the following clinical case, along with a review of the available literature. The patient is a 50-year-old woman with a history of uterine fibroids, who underwent surgery of a right inguinal hernioplasty, revealing tube-ovarian content in the hernia sac. Inguinal hernioplasty was performed using the Lichtenstein technique with preservation of adnexa, and there were no postoperative complications. In final conclusions, we consider that intraoperative finding of tube-ovarian content in inguinal hernia surgery in adult women are uncommon, and knowledge and management of this condition are necessary for the general surgeon. A high index of suspicion is required to avoid complications and provide the most optimal surgical treatment for the well-being of patients.